Trust, Voice, and Incentives : Learning from Local Success Stories in Service Delivery in the Middle East and North Africa - Brixi, Hana; Lust, Ellen; Woolcock, Michael (Washington, DC: World Bank, 2015)
This report examines the role of incentives, trust, and engagement as critical determinants of service delivery performance in MENA countries. Focusing on education and health, the report illustrates how the weak external and internal accountability undermines policy implementation and service delivery performance and how such a cycle of poor performance can be counteracted. Case studies of local success reveal the importance of both formal and informal accountability relationships and the role of local leadership in inspiring and institutionalizing incentives toward better service delivery performance.